A Case of Sinonasal Melanoma With Unusual Primary Exon 17 KIT D820G Mutation. Issue 10 (November 2016) - Pilozzi, Emanuela; Bartolazzi, Armando; Fochetti, Flavio; Duranti, Enrico; Scarpino, Stefania; Valeriani, Maurizio; Moriconi, Piero; Ruco, Luigi
Abstract : Sinonasal melanomas are rare neoplasms with poor prognosis that may harbor KIT and NRAS genes mutations. Molecular alterations represent possible targets of tailored therapeutic approaches. We describe the case of a 74-year-old patient with primary melanoma of the nasal cavity. Mutational analysis of KIT demonstrated a point missense mutation D820G in exon 17. This represents, to our knowledge, the first case of sinonasal melanoma harboring this specific KIT mutation. Although KIT mutations confer sensibility to thyrosine-kinase inhibitor, it has been proved that this is strongly dependent on the region in which this alteration occurs. Thus it seems very important to perform an accurate gene mutational analysis to provide a biological rationale to the tailored therapy.